Understanding China's Belt and Road Initiative - Yu, Hong (Singapore : Springer Nature Singapore Pte Ltd., 2024)
"This open access book provokes critical thinking regarding the most ambitious Chinese project since the founding of the Peoples Republic of China, The Belt and Road Initiative (BRI). The book presents extensive quality research and original insights in assessing the status of Chinas outbound investment and construction projects under the BRI umbrella. Referring to case studies and projects of selected countries from Southeast Asia, Central Asia, and the Middle East, the author sheds new light on the issues and problems associated with the BRI's implementation and discusses both the readjustments and prospects for the BRI. Finally, this book demarcates the limits and potential of the worlds second largest economy in pushing for the BRI, which is challenged by enormous domestic tensions and external pressures. It also identifies and analyzes potential new collaboration areas between the Belt and Road countries and China under the BRI framework in the context of the post-COVID-19 era. It provides an outstanding reference for academics, students, policymakers, and the business community working in areas of international affairs and Asian economics and development, particularly those interested in Sino-relations and Chinese power dynamics in the global world order." --
Chapter 1 Chinas Push for the BRI in a Changing World: Origins and Motivations -- Chapter 2 BRI as Chinas Platform to Push for Economic Globalisation -- Chapter 3 China-ASEAN Cooperation under the BRI -- Chapter 4 Vietnams Mixed Reactions to China and the BRI -- Chapter 5 The China-Singapore Chongqing Connectivity Project: A Cornerstone for bilateral relations -- Chapter 6 Riding on the BRI Train: Issues relating to Chinas Strengthening Ties with Cambodia.
Includes bibliographical references and index.
Keywords: China -- Commercial policy; China -- Commerce; China -- Foreign economic relations; Economic development -- China; Economic development -- Developing countries